Influência da remoção do plasma seminal na criotolerância do sêmem ovino - Dacampo, Lucas Dalle Laste (2019)
Semen cryopreservation technique has allowed the formation of genetic banks and the commercialization of gametes and embryos in different species. However, sheep cryopreserved semen when used in a cervical artificial insemination or laparoscopy presents unsatisfactory results, such as low pregnancy rate, high cos and lack of specialized labor. Given this, some alternatives are needed to reduce injuries to the cells, such as the removal of seminal plasma, which is already routine in other species. The aim of this study was to evaluate the influence of seminal plasma on semen quality during cryopreservation of sheep semen. The ejaculate of four ram was collected and evaluated for volume, color, appearance, motility. Subsequently, a pool with the ejaculates was performed and split into three groups: Control Group (CG) where semen was diluted in a traditional form, Without Seminal Plasma (WSP) in which semen was centrifuged at 4000 x g for plasma removal, and Centrifuged Control (CC) in which semen was centrifuged but not plasma withdrawn. Semen was diluted in commercial extender (OptixcellTM IMV medium), filled in 0.25mL straws at a final concentration of 400x106 sperm / mL, and straws were cooled at 5 °C for 2 hours, then exposed to nitrogen vapor for 15 minutes and stored. at -196 °C. After cryopreservation the straws were thawed at 37 °C for 20 seconds and the following evaluations were performed: sperm kinetics, plasma and acrossomal membrane integrity, mitochondrial viability, DNA fragmentation, sperm morphology, oxidative stress and fecundating capacity. The CC group was inferior to the CG and WSP groups in total and progressive motility (P = 0.05), fast (P = 0.05) and slow motility (P = 0.03). The acrosomal integrity was higher in the WSP group (P = 0.05) when compared to the CG and CC. Therefore, the removal of seminal plasma did not influence the quality of ram semen. The sperm kinetics was not affected and the WSP group preserved the integrity of the acrosomal membrane during cryopreservation, however, did not increase the fecundating capacity of sperm.